Applying the Psychological of Space in Islamic Boarding School (Case Study: Pesantren Al Mahshyar Nurul Iman) - Reza Amalia Fitriani; Djoko Murdowo; Widyanesti Liritantri (Journal of Islamic Architecture, 2023)
Adolescents have different psychological conditions and spend a lot of time in boarding schools because they must live in Islamic boarding schools where many rules and activities must be followed. The research method used in this case study is a qualitative method which consists of a survey, literature review, and data analysis. A spatial approach is taken to "read" the user of space in understanding the spaces that trigger negative psychological conditions. Negative psychological conditions were understood through interviews and literature studies. The Pesantren Al Mahsyar Nurul Iman case study has students aged 12-15 years. At the Pesantren Al Mahsyar Nurul Iman, it is necessary to pay attention to things that are based on the character and psychology of the students to create a calming, comfortable and safe environment for students who are experiencing cognitive development and changes in psychological conditions, so that students can feel at home and become more comfortable which can be taken into consideration in the design of the next pesantren. These conditions can be done by paying attention to the privacy area, creating stimulant and calming visual concepts and adding facilities to study rooms and communal areas to support the character of students who like to explore and do group activities.